2022
DOI: 10.1186/s12302-022-00600-8
|View full text |Cite
|
Sign up to set email alerts
|

The Brief Environmental Exposure and Sensitivity Inventory (BREESI): an international validation study

Abstract: Background Chemical intolerance (CI) is a condition that may result in multisystem symptoms triggered by low levels of exposure to xenobiotics such as chemical inhalants, foods, and/or drugs. The population prevalence of self-reported chemical intolerance is estimated to be between 4 and 25% across several countries. Clinicians and researchers require a brief, practical screening tool for identifying chemical intolerance. Objectives We investigated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Designed for busy office practices, the brief environmental exposure and sensitivity inventory (BREESI) is an internationally validated 3-item 1-minute screener for CI. 10,30,31 Our research has shown that 97% of persons answering "Yes" to all three items on the BREESI had high CI scores as assessed by the larger 50-item QEESI. Ninety-five (95%) of those who answered "No" to all of the BREESI items, showed no evidence of CI on the QEESI.…”
Section: Discussionmentioning
confidence: 77%
“…Designed for busy office practices, the brief environmental exposure and sensitivity inventory (BREESI) is an internationally validated 3-item 1-minute screener for CI. 10,30,31 Our research has shown that 97% of persons answering "Yes" to all three items on the BREESI had high CI scores as assessed by the larger 50-item QEESI. Ninety-five (95%) of those who answered "No" to all of the BREESI items, showed no evidence of CI on the QEESI.…”
Section: Discussionmentioning
confidence: 77%
“…CI was assessed using the Brief Environmental Exposure and Sensitivity Inventory (BREESI) [ 12 , 28 , 29 ]. The BREESI is derived from the Quick Environmental Exposure and Sensitivity Inventory (QEESI) [ 30 , 31 ], a 50-item validated questionnaire designed to identify individuals with CI.…”
Section: Methodsmentioning
confidence: 99%
“…The BREESI has excellent positive and negative predictive validity (97% and 95%, respectively), as well as sensitivity and specificity (90% and 87%, respectively). A sum score of the three items is an accurate screen for CI [ 12 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BREESI was used as a screener for CI and then the QEESI questionnaire for con rming CI status. The BREESI provides 91% sensitivity and 93% speci city in identifying CI individuals when used in combination with the QEESI (Palmer et al, , 2022Miller & Prihoda, 1999a,b). Answering "YES" to one or more BREESI questions quali ed participants to complete the 50-item QEESI.…”
Section: Methodsmentioning
confidence: 99%